CAN PROMOTED SYNTHESIS OF AMIDE DERIVATIVES:A GREEN TECHNOLOGY FOR PHARMACEUTICALS - NEERJA GUPTA; RUBY NAAZ (International Journal of Pharma and Bio Sciences, 2010)
Green technologies are required essentially to protect our environment from pollution. These techniques are potentially valuable as they reduce the need for organic solvents and also increase ‘atom economy’ by improving product selectivity and chemical yield. This method displays both economic and environmental advantages. High yields are achieved even on a gram scale, while reaction times are considerably shortened. Ceric Ammonium Nitrate (CAN) has been found to be an efficient catalyst for the solid phase green synthesis of amide derivatives of substituted carboxylic acid with urea in excellent yields under microwave irradiation conditions. Present paper reveals the method of synthesis of some amide derivatives using CAN as catalyst and their pharmaceutical applications have been reviewed.